2015
DOI: 10.1186/s12885-015-1843-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of fracture in men with prostate cancer on androgen deprivation therapy: a population-based cohort study in New Zealand

Abstract: BackgroundAndrogen deprivation therapy (ADT) administered as a prostate cancer treatment is known to exert multiple side effects including bone deterioration leading to bone fracture. The current analysis is to evaluate the burden of fracture risk in the New Zealand prostate cancer (PCa) population treated with ADT, and to understand the subsequent risk of mortality after a fracture.MethodsUsing datasets created through linking records from the New Zealand Cancer Registry, National Minimal Dataset, Pharmaceuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 30 publications
1
54
0
1
Order By: Relevance
“…One study with over 50,000 participants found that androgen deprivation therapy either through gonadotropin-releasing hormone agonist or orchiectomy increased the relative risk of fracture by 1.54 and 1.45, respectively, and when metastatic disease was excluded, the relative risk of fracture in men on a gonadotropin-releasing hormone agonist was still RR 1.37 [82]. A number of other studies have found similar results in men undergoing androgen deprivation therapy for prostate cancer [8587]. Overall, with the data from observational studies suggesting a role of testosterone in osteoporotic fractures in men combined with proven increased fracture risk in men undergoing androgen deprivation, it seems likely that low testosterone is indeed associated with fracture risk in older men.…”
Section: The Effect Of Male Hypogonadism On Bone Quality and Fractmentioning
confidence: 86%
“…One study with over 50,000 participants found that androgen deprivation therapy either through gonadotropin-releasing hormone agonist or orchiectomy increased the relative risk of fracture by 1.54 and 1.45, respectively, and when metastatic disease was excluded, the relative risk of fracture in men on a gonadotropin-releasing hormone agonist was still RR 1.37 [82]. A number of other studies have found similar results in men undergoing androgen deprivation therapy for prostate cancer [8587]. Overall, with the data from observational studies suggesting a role of testosterone in osteoporotic fractures in men combined with proven increased fracture risk in men undergoing androgen deprivation, it seems likely that low testosterone is indeed associated with fracture risk in older men.…”
Section: The Effect Of Male Hypogonadism On Bone Quality and Fractmentioning
confidence: 86%
“…Consequently, levels of oestradiol (produced via testosterone aromatization to oestradiol) are also severely reduced. Although testosterone is the dominant male sex steroid, there is good epidemiologic evidence that (as in women) bioavailable oestradiol levels more closely correlate with BMD in men, with abrupt lowering of oestradiol levels as occurs with ADT leading to bone loss, bone microarchitectural deterioration and increased fracture risk . More recently, both abiraterone acetate (which inhibits the key enzyme that catalyses androgen biosynthesis [CYP17]) and enzalutamide (an androgen receptor antagonist) have been developed and approved for the treatment of men with castration‐resistant prostate cancer.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Numerous systematic reviews and meta‐analyses of observational studies have therefore suggested that men who have received this treatment are at risk of the complications of testosterone deficiency. These are comparable to men with hypogonadism due to other causes and include ED, depression, type 2 diabetes, adverse changes in body composition, increased risk of fractures and decreased bone mineral density, and cardiovascular disease . There are numerous interventions available to manage these adverse effects of ADT.…”
Section: Introductionmentioning
confidence: 99%